7x+9(1-2x)=4-7(x-1)

Simple and best practice solution for 7x+9(1-2x)=4-7(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+9(1-2x)=4-7(x-1) equation:


Simplifying
7x + 9(1 + -2x) = 4 + -7(x + -1)
7x + (1 * 9 + -2x * 9) = 4 + -7(x + -1)
7x + (9 + -18x) = 4 + -7(x + -1)

Reorder the terms:
9 + 7x + -18x = 4 + -7(x + -1)

Combine like terms: 7x + -18x = -11x
9 + -11x = 4 + -7(x + -1)

Reorder the terms:
9 + -11x = 4 + -7(-1 + x)
9 + -11x = 4 + (-1 * -7 + x * -7)
9 + -11x = 4 + (7 + -7x)

Combine like terms: 4 + 7 = 11
9 + -11x = 11 + -7x

Solving
9 + -11x = 11 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
9 + -11x + 7x = 11 + -7x + 7x

Combine like terms: -11x + 7x = -4x
9 + -4x = 11 + -7x + 7x

Combine like terms: -7x + 7x = 0
9 + -4x = 11 + 0
9 + -4x = 11

Add '-9' to each side of the equation.
9 + -9 + -4x = 11 + -9

Combine like terms: 9 + -9 = 0
0 + -4x = 11 + -9
-4x = 11 + -9

Combine like terms: 11 + -9 = 2
-4x = 2

Divide each side by '-4'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| B=p+4a+33c | | 3b+2b-2=13 | | 3x-17+2x+1=25-x | | 3x-17+2x+1=25 | | 18+3(90-x)=90 | | x-49=8 | | s(t)=5t^2+15t | | (9x+4)-(-9x+8)= | | 77/11(5-3) | | 2[x+6]=2[-x+6.5] | | 4x+5=3x-14 | | x(4+3)=5-8x | | -4a=14a-12[4a+10] | | (x+7)(5)=45 | | -3[2u+5]+3.5u=-1u | | 100-50/5•10 | | f(7)=8x-3 | | 2b^2-9b-45=0 | | -7+8[5-3s]=3[7-9s] | | 4g+3[g-2]=-5[g-4]-g | | N/18=6/8 | | 0=×-9/x^2-81 | | 2b+4[b-6]=-2[2b-14]+98 | | 5x-7+x=3 | | 8x=540 | | 1/6[6w-12]=6-2[w-2] | | 4x=540 | | 19p+q-6p+8q= | | 2/5c-12=-32 | | 1/6[6w-12]=6-2[w-2 | | 8yt+x=3y+9x-5xy | | 49t^2=100 |

Equations solver categories